Serological and molecular detection of infectious laryngotracheitis virus in chickens in Central Gondar Zone, Ethiopia - Adam, Omima; Oladele, Omolade A.; Yimam, Tadesse Mihret; Getachew, Belayneh; Deresse, Getaw; Birhanu, Kenaw; Legesse, Abinet; Tefera, Takele Abayneh; Bitew, Molalegne (Frontiers in Veterinary Science, 2025)
IntroductionInfectious laryngotracheitis (ILT) is a highly contagious upper respiratory tract disease of chickens caused by a Gallid herpesvirus 1 (GaHV-1). The current study was to establish molecular evidence of Infectious laryngotracheitis virus (ILTV) in the Amhara region, Ethiopia, and determine its seroprevalence in areas of high chicken population and assess the risk factors associated with the disease.MethodsSerological study was conducted on 385 serum samples collected from commercial and backyard chickens in the study area, and the presence of antibodies against ILTV was determined by indirect ELISA. In addition, oropharyngeal swab samples were collected from chickens suspected of ILT infection and inoculated into embryonated chicken eggs through the Chorioallantoic membrane (CAM) route for isolation of the virus. Isolates were confirmed using polymerase chain reaction (PCR) upon amplification of ICP4 gene. Furthermore, potential factors were recorded, and their association with the virus seropositivity assessed.ResultsThe overall seroprevalence of ILT in the study area was 19.4%. A significant difference (P < 0.05) among districts, and between commercial (14.2%) and backyard (22.9%) production systems was observed (P < 0.05). Significantly higher seroprevalence was observed in layers compared to broilers and dual-purpose chickens however, there were no significant differences in prevalence based on age and sex. Of all (n = 27) tested oropharyngeal swab samples, four were positive for ILTV by PCR targeting a 688 bp region of ICP4 gene. Three of the PCR positive cases were from backyard chickens, while one was from commercial chicken farms. Based on oropharyngeal samples tested using PCR, a quarter of the samples were positive for ILT.DiscussionThe result confirms the presence of ILT infection in the Amhara region of Ethiopia using serological and molecular methods. The study shows chickens shed the virus potentially spreading the infection to other birds. Vaccination strategy, strict biosecurity measures, rapid diagnosis, and detection of latent carriers are recommended to control and eradicate the disease. Further studies on clinical cases and the molecular characterization of the target gene are needed to identify circulating strains.